Acquisition Of Source And Use Of Capital Work By Analyzing Financial Report - Ni Made Sri Ayuni; I Gusti Ngurah Kadek Hardiana Putra (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to determine the sources and uses of working capital by analyzing the financial reports of the Padang Bulia Traditional Village LPD. The data used in this study are balance sheet data and financial reports obtained directly from the Padang Bulia Traditional Village LPD. This research method is a horizontal method used to compare company financial reports from different years, namely the 2018- 2022 period. Analysis of sources and uses of working capital is a very important financial analysis for companies/business entities. The results of this analysis show that the analysis of the sources and use of working capital LPD Padang Bulia Traditional Village for the 2018-2022 period has been effective and efficient with increases and decreases in working capital must be the same in reports on changes in working capital, reports on sources and use of working capital, liquidity ratios and working capital turnover ratio.